Development and evaluation of various modes of human robot interface for mobile robot - Yeong, Che Fai; H. M. Amin, Shamsudin; Fisal, Norsheila; L. M. Su, Eileen (2005)
In the near future, robots are expected to be more acceptable and commonly used by human beings. Therefore, human robot interface (HRI) is essential to enable efficient and effortless communication between humans and robots. The main objective of this work is to develop, evaluate and then to improve current HRIs, such as teleoperation, manual, speech and vision interaction, by eliminating the weakness in these techniques. An enhanced teleoperation technique using portable devices was introduced as a better HRI technique for human to wirelessly control and communicate with mobile robot. Through this method, user can use their portable device to communicate with the robot as long as they are using the same wireless communication protocol and wireless devices. The portable devices tested in the project were the Personal Digital Assistant (PDA), a laptop and a remote PC. Comparison between different HRIs through experiments shows that portable device interaction is more reliable, efficient and easy to use compared to manual, speech and vision interaction.